Inhibition of juvenile hormone synthesis in mosquitoes by the methylation inhibitor 3-deazaneplanocin A (DZNep) - Nouzova, Marcela; Michalkova, Veronika; Ramirez, Cesar E; Fernandez-Lima, Francisco; Noriega, Fernando G (Insect biochemistry and molecular biology, 2019)
Juvenile hormone (JH), synthesized by the corpora allata (CA), controls development and reproduction in mosquitoes through its action on thousands of JH-responsive genes. These JH-dependent processes can be studied using tools that increase or decrease JH titers in vitro and in vivo. Juvenile hormone acid methyl transferase (JHAMT) is a critical JH biosynthetic enzyme. JHAMT utilizes the methyl donor S-adenosyl-methionine (SAM) to methylate farnesoic acid (FA) into methyl farnesoate (MF), releasing the product S-adenosyl-L-homocysteine (AdoHcy), which inhibits JHAMT. S-adenosyl-homocysteine hydrolase (SAHH) catalyzes AdoHcy hydrolysis to adenosine and homocysteine, alleviating AdoHcy inhibition of JHAMT. 3-deazaneplanocin A (DZNep), an analog of adenosine, is an inhibitor of SAHH, and an epigenetic drug for cancer therapy. We tested the effect of DZNep on in vitro JH synthesis by CA of mosquitoes. DZNep inhibited JH synthesis in a dose-response fashion. Addition of MF, but not of FA relieved the inhibition, demonstrating a direct effect on JHAMT. In vivo experiments, with addition of DZNep to the sugar ingested by mosquitoes, resulted in a dose-response decrease in JH synthesis and JH hemolymphatic titers, as well as expression of early trypsin, a JH-dependent gene. Our studies suggest that DZNep can be employed to lower JH synthesis and titer in experiments evaluating JH-controlled processes in mosquitoes.
Keywords: adenosin; Insect Proteins; metylace; Methylation; Juvenile Hormones; hmyzí proteiny; Animals; Adenosine; methyltransferasy; Female; ženské pohlaví; Aedes; juvenilní hormony; zvířata; Methyltransferases